2000
DOI: 10.1063/1.480931
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of an irreversible catalytic reaction to periodic variation of the reactant’s pressure

Abstract: Influence of extended interactions on the surface dynamics in the catalytic CO oxidation on Pt single crystal substrateOn the influence of reactant's induced surface transformations in the behavior of a heterogeneously catalyzed dimer-monomer reaction model

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…One way to perturb the catalytic oxidation process in order to increase the CO 2 production is by switching the external pressure back and forth across the discontinuous transition y 2 (k) [5,6,7,8,9]. It has been shown that when the ZGB system without desorption is quickly oscillated between the low and high θ CO phases by a periodic variation of the external pressure, there is considerable enhancement of the catalytic activity [13,14]. The period and amplitude of the driving pressure must be calibrated very carefully in order to avoid driving the system irreversibly toward the CO poisoned state.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…One way to perturb the catalytic oxidation process in order to increase the CO 2 production is by switching the external pressure back and forth across the discontinuous transition y 2 (k) [5,6,7,8,9]. It has been shown that when the ZGB system without desorption is quickly oscillated between the low and high θ CO phases by a periodic variation of the external pressure, there is considerable enhancement of the catalytic activity [13,14]. The period and amplitude of the driving pressure must be calibrated very carefully in order to avoid driving the system irreversibly toward the CO poisoned state.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that when the ZGB system without desorption is quickly oscillated between the low and high θ CO phases by a periodic variation of the external pressure, there is considerable enhancement of the catalytic activity [13,14]. The period and amplitude of the driving pressure must be calibrated very carefully in order to avoid driving the system irreversibly toward the CO poisoned state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Near the coexistence line between the active and the CO poisoned phase, the decay times of the metastable state are different if the ZGB-k model is driven into the active phase from the CO poisoned state or vice versa [7]. This asymmetry of the lifetimes, together with studies that indicate that it is possible to increase the efficiency of catalytic reactions by forcing the system by a periodic external pressure that switches back and forth around the discontinuous transition [10,11,12], inspired us to subject the system to a square-wave periodic CO pressure that stays for a time t d in the high-production region and t p in the low-production region. We showed that t p and t d can be tuned to significantly enhance the time-averaged catalytic activity of the system [6].…”
Section: Introductionmentioning
confidence: 96%
“…µε περιοδική τροφοδοσία που επιφέρει ταλάντωση. Η ϑεωρητική µελέτη των A. C. López και E. V. Albano δίνει ένα παράδειγµα αύξησης της απόδοσης κατά την καταλυτική οξείδωση του CO µε περιοδική αυξοµείωση της πίεσης[76].Το «χάσµα» της µελέτης αντιδράσεων σε επιφάνεια και της καθηµερινής ετερογενούς κατάλυσηςΗ κατανόηση του ϱόλου του καταλύτη στις αρχές της ετερογενούς κατάλυσης γινόταν εµπειρικά, ακολουθώντας την οδό της δοκιµής και λάθους. Αργότερα άρχισαν να γίνονται κινητικές µελέτες σε συνδυασµό µε τεχνικές χαρακτηρισµού του καταλύτη ex situ.…”
unclassified